Medication Review: What's in a Name and What Is It about? - Anneleen Robberechts; Maja Brumer; Victoria Garcia-Cardenas; Niurka M. Dupotey; Stephane Steurbaut; Guido R. Y. De Meyer; Hans De Loof (MDPI AG, 2024)
Background: Medication review is a multifaceted service aimed at optimizing the use of medicines and enhancing the health outcomes of patients. Due to its complexity, it is crucial to clearly describe the service, its variants, and its components to avoid confusion and ensure a better understanding of medication review among healthcare providers. Aim: This study aims to bring clarity to the origins, definitions, abbreviations, and types of medication reviews, together with the primary criteria that delineate key features of this service. Method: A narrative review approach was employed to clarify the diverse terminology associated with "medication review" services. Relevant references were initially identified through searches on PubMed and Google Scholar, complementing the existing literature known to the authors. Results: The study uncovers a complicated and sometimes convoluted history of "medication review" in different regions around the world. The initial optimization of medicine use had an economic purpose before evolving subsequently into a more patient-oriented approach. A selection of abbreviations, definitions, and types were outlined to enhance the understanding of the service. Conclusions: The study underscores the urgent need for comprehensive information and standardization regarding the content and quality of the services, collectively referred to as "medication review".